2019
DOI: 10.30699/jergon.7.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Relationship Between Job Burnout and Employee Productivity

Abstract: Background and Objectives: The progress and rebound of organizations depends on their productivity. Many factors affect the organization's productivity; identifying these factors the organization's deterrence can be prevented. In this study, the relationship between job burnout and employee productivity has been investigated. Methods: This research is applied and its statistical population is 1265 people in Shariati and Kharazi hospitals. 294 of these employees were selected by Convenience sampling method cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thus, it can be assumed that burnout (personal accomplishment), autocratic leadership styles and job performance were related to each other during the critical period of MCO due to COVID-19 in Malaysia. The present findings seem consistent with other research (Wafaa, 2019, Mirkamali et al, 2019Abdullah & Yuen, 2011), which also aligns with this study. They found that the feeling of inefficacy or reduced personal accomplishment is assumed to be related to job performance.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, it can be assumed that burnout (personal accomplishment), autocratic leadership styles and job performance were related to each other during the critical period of MCO due to COVID-19 in Malaysia. The present findings seem consistent with other research (Wafaa, 2019, Mirkamali et al, 2019Abdullah & Yuen, 2011), which also aligns with this study. They found that the feeling of inefficacy or reduced personal accomplishment is assumed to be related to job performance.…”
Section: Discussionsupporting
confidence: 94%
“…The result did not support the hypothesis, and the researcher concluded that there was no correlation between the variables and the relationship was proven weak. Over the year, several studies thus far have linked burnout with job performance (Wafaa, 2019;Mirkamali et al, 2019;Gorji, 2011;Ashtari et al, 2009). However, this is the most exciting finding where this current study does not support the previous research.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Burnout and deterioration of employee health ultimately reduces quality of service and health of patients with the disease ( 7 , 8 , 12 ) and thus creating a vicious cycle that reduces the country’s ability to deal with COVID-19. Research in the medical sector shows that high workload, insufficient support, lack of adequate equipment, and death of patients can cause burnout and eventually mental and physical illness in employees ( 13 - 15 ). Therefore, burnout is one of the first issues that should be considered especially when the disease is continuous and prolonged.…”
mentioning
confidence: 99%